Religion, history and place in the origin of settled life - Hodder, Ian, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Exploring the role of religion in the origin of settled life in the Middle East and focusing on repetitive house or cult building construction in the same place. Working at several important sites it's argued that religious factors had significant effects on timing and stability of economics.--Provided by publisher.
1. Simulating Religious Entanglement and Social Investment in the Neolithic / Wesley J. Wildman -- 2. Creating Settled Life: Micro-Histories of Community, Ritual, and Place---the Central Zagros and Catalhuyuk / Wendy Matthews -- 3. Long-Term Memory and the Community in the Later Prehistory of the Levant / Anna Belfer-Cohen -- 4. Establishing Identities in the Proto-Neolithic: "History Making" at Gobekli Tepe from the Late Tenth Millennium cal bce / Devrim Sonmez -- 5. Re-presenting the Past: Evidence from Daily Practices and Rituals at Kortik Tepe / Vecihi Ozkaya -- 6. Sedentism and Solitude: Exploring the Impact of Private Space on Social Cohesion in the Neolithic / Gunes Duru -- 7. "Every Man's House Was His Temple": Mimetic Dynamics in the Transition from Asikli Hoyuk to Catalhoyuk / Mark R. Anspach -- 8. Interrogating "Property" at Neolithic Catalhoyuk / Rosemary A. Joyce -- 9. Ritualization of Daily Practice: Exploring the Staging of Ritual Acts at Neolithic Catalhoyuk, Turkey / Christina Tsoraki -- 10. Virtually Rebuilding Catalhoyuk History Houses / Nicola Lercari.
Keywords: Social archaeology -- Middle East; Dwellings -- Middle East -- Religious aspects; Economic anthropology -- Middle East; Spatial analysis (Statistics) in archaeology; Excavations (Archaeology) -- Middle East; Neolithic period -- Middle East; Çatal Mound (Turkey); Antiquities, Prehistoric -- Turkey -- Çatal Mound